Giant Cell Tumor Of The Sacrum- Multimodality Management Of A Challenging Disease - Rege, Ishant; Singh, Neeraj; Punia, Prashant; Chugh, Ashish; Gotecha, Sarang; Gaud, Jayant (Journal of Neonatal Surgery, 2025)
Giant cell tumor (GCT) of the sacrum is a rare primary bone tumour located in a challenging anatomical region. Due to its proximity to nerve roots and complex anatomical positioning, there is no widely accepted standard treatment. This article presents a case of a teenage female with sacral GCT who underwent a multimodality treatment approach at our institute. The patient presented with progressive lower back pain and radiculopathy. Imaging revealed a large lytic mass extending into the sacral spinal canal and surrounding structures. After a confirmed histopathological diagnosis, multidisciplinary treatment plan was implemented, including pre-operative embolization followed by surgical excision with spinal stabilization. Pre-operative embolization significantly reduced vascularity and intra-operative blood loss, allowing for successful total excision and preservation of neurological function. Postoperative recovery was uneventful. This case highlights the importance of a multimodal strategy combining embolization and surgical excision in managing sacral GCT, particularly in complex anatomical regions where en bloc resection is challenging.